KOMUNIKASI LINGKUNGAN MELALUI MAHARAGU SUNGAI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PROGRAM REVITALISASI SUNGAI KOTA BANJARMASIN - Novaria Maulina; Atika Rusli (Universitas Lambung Mangkurat, 2021)
The city of Banjarmasin is a city known as the city of a thousand rivers, however the problem faced by the Banjarmasin City Government is the number of rivers which became shallow and narrow because of the people habits who live on the riverbank. Their habits are throwing garbage and household waste into the river. So that the Banjarmasin City government initiated activities aimed at restoring the function of the river or called river revitalization. Through this paper, the researcher described how communication approach undertaken by the Banjarmasin City Environmental Department to increase community awareness and participation in the river revitalization program. Furthermore, the result found through qualitative approach with interview techniques, observation and documentation was the Banjarmasin City Environmental Department had personal and persuasive communication and involving river stakeholders as an opinion leader to increase community participation in maintaining rivers cleanliness and developing rivers as a potential tourist destination.Keywords: Environmental Communication, Community Participation, Maharagu Sungai.